2010
DOI: 10.1007/s00264-010-1047-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between the sagittal femoral stem alignment and the resulting femoral head centre in total hip arthroplasty

Abstract: Adequate stem alignment is essential for the success of Total Hip Arthroplasty (THA) to avoid dislocation and impingement. One factor that has not been sufficiently investigated so far is the stem tilting in the sagittal plane, which has an influence on the position of the centre of the femoral head and thus also on prosthesis torsion. We aimed to evaluate sagittal stem position using 3D-CTs in patients with THA and to develop a mathematical-geometrical model to simulate the functional correlation between sagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 13 publications
1
33
0
2
Order By: Relevance
“…Sagittal stem alignment was calculated from the angle between the stem axis and the proximal femoral axis in the sagittal plane ( Fig. 3a) [23]. When the stem axis was anteriorly tilted compared to the proximal femoral axis, sagittal stem alignment was defined as having an anterior tilt.…”
Section: Measurement Of Each Parametermentioning
confidence: 99%
“…Sagittal stem alignment was calculated from the angle between the stem axis and the proximal femoral axis in the sagittal plane ( Fig. 3a) [23]. When the stem axis was anteriorly tilted compared to the proximal femoral axis, sagittal stem alignment was defined as having an anterior tilt.…”
Section: Measurement Of Each Parametermentioning
confidence: 99%
“…Regarding the sagittal stem tilt, the present results suggest that the anterior bowing of proximal femur did not vary widely according to patient background characteristics, including sex, gender, and diagnosis. Previous computer simulation studies assumed a sagittal stem tilt of 0°–3° , and previous studies investigating sagittal stem tilt reported a mean sagittal tilt of 5.2° based on the proximal femoral shaft axis and 5.7° based on the mechanical axis . However, as these previous studies evaluated the European population , and considering the possibility of racial differences in anterior bowing of the femur , it may be necessary to investigate the average sagittal femoral tilt of each race in separate simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous computer simulation studies assumed a sagittal stem tilt of 0°-3° (6-9), and previous studies investigating sagittal stem tilt reported a mean sagittal tilt of 5.2° based on the proximal femoral shaft axis (13) and 5.7° based on the mechanical axis (14). However, as these previous studies evaluated the European population (13,14), and considering the possibility of racial differences in anterior bowing of the femur (18), it may be necessary to investigate the average sagittal femoral tilt of each race in separate simulation studies. Regarding the coronal stem tilt, multiple regression analysis revealed a significant correlation between lower coronal tilt and older age in the anatomical coordinate system.…”
Section: Alignment Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…It relies on a multipoint fixation with cortical contact at the medial calcar, the lateral rim of the resected neck, as well as the distal appendix in the posterior lateral subtrochanteric region. Müller et al (2011) and described the effect of implant tilt and implant rotation on the reconstruction of the center of rotation in hip reconstruction, respectively. This final position determines the position of the implants in the femoral neck, probably changing offset and leg length as well as the center of rotation.…”
Section: Introductionmentioning
confidence: 99%